(untitled) (Journal of the College of Basic Education, 2022)
Water is one of the most prominent poetic symbols used by poets throughout the ages. which is a symbolHe is represented in all myths, foremost among them are the myths of Mesopotamia, such as Talmon, which explainsthe relationship between earth (femininity) and water (masculinity); There is no way to sever the relationship between them because thatleads to the fading of life; Homer previously described (the river) as the father of beings (1); for what it involvesIt has dominance, power, tanbar, and value.Some of the poems of the poet Abd al-Razzaq al-Rubaie begin with the use of the poetic water since the grape of the title »The watery title adopted by the poet continues to produce significance within the poetic text from its inceptionto its end;